The hydrogeology of the Aðaldalur region, NE Iceland in terms of hydrogeochemistry and stable water isotopes - Þrúður Helgadóttir 1984- (2019)
The stable isotopes of water (δD and δ18O) and hydrogeochemistry (Cl and B) of hot and cold groundwater (springs and boreholes) as well as surface waters (rivers, streams and lakes) were used to trace the origin of these water sources, mixing of waters types, the degree of primary rock leaching and the presence of potential palaeowater in the region. The waters showed a large range in temperature (2.8-97.5 °C), pH (7.14-10.58) and Cl concentration (1.58 – 1709 ppm) and generally low B concentration (<0.125 ppm). Isotope values were also highly variable, with δD content ranging from -127.8‰ to -58.2‰ and, δ18O from -17.09‰ to -8.11‰. Most shallow groundwaters and small streams were traced to a local source while the two main rivers of the region were found to correlate with precipitation around Lake Mývatn (Laxá) and the northern Vatnajökull region (Skjálfandafljót). The chemistry and the isotopic signature of the river Laxá remained stable all the way from its source towards the sea, whereas the river Skjálfandafljót showed more variability. A linear relationship between δD and Cl was observed with decreasing deuterium and chloride content, for surface water samples and the shallow, cold groundwater samples as expected for pure precipitation with increasing inland and altitude effect. Geothermal waters with a deeper source and highly depleted deuterium content were found in several locations within the low lying areas in the valleys within the study area. This includes Húsavík, Árnes, Hafralækur, Hveravellir, Laugar and Stóru Tjarnir. It is suggested that a component of these water, of a variable proportion, is made up of precipitation that recharged the aquifers during a time when climate was significantly colder than today. These water samples showed a negative correlation between δD and Cl suggesting mixing between water types (modern water, pre-Holocene water and, in the case of Húsavík, saline water). Hydraulic connection was found between the water in Árnes and Hafralækur, but the water in Árnes had ...